2011
DOI: 10.5194/angeo-29-331-2011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple magnetic dipolarizations observed by THEMIS during a substorm

Abstract: Abstract. The magnetic field dipolarization in the vicinity of substorm onset and during substorm expansion phase during the period of 06:00-06:40 UT on 15 February 2008 is investigated with observations from multiple probes of THEMIS. It is found that the magnetic dipolarization at the substorm onset (the onset time was about 06:14 UT) was not accompanied by obvious magnetic disturbance and ion bulk speed variation. The magnetic dipolarizations taking place during the substorm expansion phase observed by P4∼(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Some have suggested that it is correlated with earthward flux transport which is piled up at the near tail [ Shiokawa et al , 1997; Birn et al , 1999]. Others, however, claim that dipolarization does not have a one‐to‐one relationship with braking of earthward bulk flows [ Lui et al , 2008; Duan et al , 2011] and that near‐Earth dipolarization is a non‐MHD process [ Lui et al , 1999].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Some have suggested that it is correlated with earthward flux transport which is piled up at the near tail [ Shiokawa et al , 1997; Birn et al , 1999]. Others, however, claim that dipolarization does not have a one‐to‐one relationship with braking of earthward bulk flows [ Lui et al , 2008; Duan et al , 2011] and that near‐Earth dipolarization is a non‐MHD process [ Lui et al , 1999].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…We identify dispersionless ion injections at 12:40 UT from two LANL satellites (LANL91 and LANL94), which are located at nightside at magnetic local time (MLT) = 1.33 and MLT = 22.02. The B z -GSE (Hp component) sharply increases at GOES, indicating the dipolarization process associated with injection [Nagai, 1982;Lui et al, 1999;Duan et al, 2011]. A clear "growth phase dropout" is observed at LANL94.…”
Section: Data Set and The Event Selectionmentioning
confidence: 92%
“…(2) The injections occurred during the storm main phases. The B z -GSE (Hp component) sharply increases at GOES, indicating the dipolarization process associated with injection [Nagai, 1982;Lui et al, 1999;Duan et al, 2011]. (b) The dispersionless injection onset time can be well identified.…”
Section: Data Set and The Event Selectionmentioning
confidence: 96%
“…It has been shown that a substorm may have multiple onsets [ Murphy et al , ]. This has been established from the ground geomagnetic field perturbations observed from the ground [ Pytte et al , ], auroral intensifications [ Keiling et al , ; Pu et al , ], global magnetic field dipolarizations in the near‐Earth magnetotail [ Duan et al , ; Palin et al , ], and substorm injections into geosynchronous orbit [ Nagai et al , ]. Previous studies also suggest that multiple auroral intensifications are related to multiple bursty bulk flows [ Nishimura et al , ].…”
Section: Introductionmentioning
confidence: 99%